Memory and tradition in the book of Numbers - Leveen, Adriane (Cambridge University Press, 2008)
In Memory and Tradition in the Book of Numbers, Adriane Leveen offers a rereading of the fourth book of Moses. Leveen examines how the editors of Numbers created a narrative of the forty-year journey through the wilderness to control understanding of the past and influence attitudes in the future. The book explores politics, collective memory and the strategies used by its priestly editors to convince the children of Israel to accept priestly rule. Leveen considers the dynamics of the transmission of tradition, memory and values in an atmosphere of crisis as a generation witnessed its parents die in the wilderness yet chose to live in the promised land in fulfilment of God's vision.